2020
DOI: 10.1055/s-0040-1712341
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Peak Expiratory Flow Rate with Waist Circumference, Hip Circumference, and Waist-to-Hip Ratio in Young Adults

Abstract: Introduction It has been observed that respiratory problems and the consequent pulmonary dysfunction are associated with an increase in waist circumference (WC), a measure of obesity. Both comorbidities result in changes in the overall health, quality of life, and life span. The literature shows that body fat distribution can affect pulmonary function. Pulmonary function test (PFT) is a basic and essential tool for the diagnosis and assessment of pulmonary dysfunction, lung diseases, and treatment effects. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 14 publications
1
5
1
Order By: Relevance
“…A positive correlation was found between the waist to hip ratio (WHR) and PEFR (p<0.01) when the combined data were studied, however, no correlation was found in the data categorized for genders. This finding is in contrast with a previous study [ 17 ], which suggested that WHR and WC affect the PEFR in males but not in females, and other anthropometric measures such as height do not affect it. We believe our work supersedes this study, as we have conducted a more thorough statistical analysis.…”
Section: Discussioncontrasting
confidence: 99%
“…A positive correlation was found between the waist to hip ratio (WHR) and PEFR (p<0.01) when the combined data were studied, however, no correlation was found in the data categorized for genders. This finding is in contrast with a previous study [ 17 ], which suggested that WHR and WC affect the PEFR in males but not in females, and other anthropometric measures such as height do not affect it. We believe our work supersedes this study, as we have conducted a more thorough statistical analysis.…”
Section: Discussioncontrasting
confidence: 99%
“…BW and BMI are best indicators of overall adiposity, whereas PBF, WC and WHR are the measures of central obesity and indicate adverse outcomes of cardiorespiratory morbidity. 17 In the current study, a statistically significant positive association was seen between PEFR and BH, which is in line with studies conducted in Pakistan and Malaysia. 8,18 The most probable reason for higher PEFR in taller subjects might be because of the greater chest diameter, more development of the airways and expiratory muscles.…”
Section: Discussionsupporting
confidence: 92%
“…24 The current results are also in line with another Indian study which reported negative association of PEFR values with WHR in the male gender only, but the finding was not consistent for the female gender. 17 Interestingly, when the aforementioned study analysed the combined data for both genders simultaneously, it found positive relation of PEFR with WHR. 17 The current findings revealed significant positive association of PEFR with WC, which was reported earlier by an Indian study 17 .…”
Section: P R O V I S I O N a L L Y A C C E P T E D F O R P U B L I C ...mentioning
confidence: 90%
See 2 more Smart Citations